Minimizing total earliness and tardiness on re-entrant batch processing machine with time windows. Issue 2 (4th March 2018) - Jia, Wenyou; Chen, Hao; Liu, Li; Li, You
ABSTRACT: The time window (TW) generalizes the concept of due date. The semiconductor wafer fabrication system is currently one of the most complex production processes, which has typical re-entrant batch processing machine (RBPM). RBPM is a bottleneck. This paper addresses a scheduling of RBPM with job-dependent TWs. According to a general modelling, an improved and new job-family-oriented modelling of the decomposition method that is based on the slack mixed integer linear programming is proposed. First, the complicated scheduling problem of RBPM is divided into sub-problems, which are executed circularly. Then, each one consists of updating, sequencing and dispatching. The objective is to minimize the total earliness and tardiness for job-dependent TWs. In order to evaluate the proposed modelling, the experiments are implemented on the real-time scheduling simulation platform and optimization toolkit ILOG CPLEX. The results show that the improved modelling obtains better solutions in less computation time.